Cross-border Activities Associated With Pattern of Amphetamine-type Stimulants Usage Among Drug Users in Southwest of China - Mingmei Zhang Master; Jiashuang Li Master; Jianhua Fan MBBS; Dongli Feng MBBS; Qun Li Master; Songyuan Tang PhD; Jing Li PhD (SAGE Publishing, 2023)
Cross-border activities are possibly associated with the use of amphetamine-type stimulants (ATS), this study was to explore poly-substance of ATS use and influencing factors among ATS use populations in southwest China. A cross-sectional study was conducted by response driven and continuous samplings from January to July 2021. Descriptive, univariate and logistic regression were carried out. ATS users accounted for 95.6% of the target population, of whom one-third had cross-border experiences with 4.1% of the cross-border purchase of drugs. ATS users were mainly over 31 years old (53.9%), male (98.7%), minority (79.1%), and unmarried (72.7%). Cross-border users consumed more ketamine (8%) and methamphetamine (40%) ( P  < .05). After adjusting for socioeconomic-demographic factors, cross-border activity [OR: 0.336 (0.141, 0.799)], occupation [OR: 0.273 (0.080, 0.929)], injecting drug behavior [OR: 6.239 (1. 087, 35.811)], frequency [OR: 0.251 (0.073, 0.859)], and ATS use location [OR: 2.915 (1.040, 8.168)] were possible factors influencing ATS use patterns ( P  < .05). Cross-border activity may be associated with polydrug use, especially predominantly methamphetamine use, among ATS users along the Southwest border. It implied that the focus of drug prevention and control in border areas should be on cross-border populations.